Joffre Dumazedier and the definition of leisure. Issue 2 (4th May 2019) - Veal, A.J.
Abstract : One of the most widely cited definitions of leisure is that presented by Joffre Dumazedier, originally published in 1962 and based on three functions of leisure identified in his empirical research in France. Three issues are addressed in this paper. First, aspects of the English translation of the definition, published in the USA in 1967, are found to be inappropriate and misleading. Second, attention is drawn to the unexplained omission of experiential features of leisure, also identified in Dumazedier's research. Third, it is observed that, in the 1970s, Dumazedier disavowed his original definition and replaced it with a more exclusive perspective identifying him with the 'Leisure Aristotelians'. Possible reasons for the original omission of experiential dimensions and for Dumazedier's decision to replace his definition with a very different one are discussed, together with consideration of the lack of attention given to these matters by leisure studies scholars.